2014
DOI: 10.1016/j.chembiol.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pharmacological AMP Deaminase Inhibition and Ampd1 Deletion on Nucleotide Levels and AMPK Activation in Contracting Skeletal Muscle

Abstract: AMP-activated protein kinase (AMPK) plays a central role in regulating metabolism and energy homeostasis. It achieves its function by sensing fluctuations in the AMP:ATP ratio. AMP deaminase (AMPD) converts AMP into IMP, and the AMPD1 isoenzyme is expressed in skeletal muscles. Here, effects of pharmacological inhibition and genetic deletion of AMPD were examined in contracting skeletal muscles. Pharmacological AMPD inhibition potentiated rises in AMP, AMP:ATP ratio, AMPK Thr172, and acetyl-CoA carboxylase (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 56 publications
2
35
2
Order By: Relevance
“…During the revision of this report, other reports indicated that AMPD1 deficient mice showed only moderate increase in AMPK activation despite increase in AMP levels and AMP/ATP ratio and that there were no favorable metabolic phenotype in AMPD1 deficient mice after HFD challenge [ 13 , 14 ]. We think that different protocol for HFD challenge created different results and that further study is awaited for delineating the importance of AMPD1 on insulin metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of this report, other reports indicated that AMPD1 deficient mice showed only moderate increase in AMPK activation despite increase in AMP levels and AMP/ATP ratio and that there were no favorable metabolic phenotype in AMPD1 deficient mice after HFD challenge [ 13 , 14 ]. We think that different protocol for HFD challenge created different results and that further study is awaited for delineating the importance of AMPD1 on insulin metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In a more novel approach, inhibition of AMP deaminase (AMPD) has been tested as yet another way to increase intracellular AMP. AMPD converts AMP into IMP, so its inhibition also increases AMP pools, which in turn activate AMPK (Plaideau et al, 2014). Indeed, one report suggested that metformin may control AMP levels via effects on AMPD (Ouyang et al, 2011).…”
Section: Therapeutic Activation Of Ampkmentioning
confidence: 99%
“…AMP deaminase catalyzes the deamination of AMP to IMP. AMP deaminase inhibition leads to an increase in AMP, an increased AMP:ATP ratio, and increased activation of AMP-activated protein kinase, a critical regulator of cellular energy homeostasis (Plaideau et al, 2014). We found several substrates of AMPK that were phosphorylated in a manner consistent with AMPK activation including TBCD1, GEF-H1, and MYPT1 ( Figure 5F).…”
Section: Phosphorylationmentioning
confidence: 86%
“…AMP deaminases control cellular levels of AMP, which are in turn sensed by AMPK. AMPK and AMP demainases have been demonstrated to counteract each other; silencing of AMPK activates AMP deaminase activity and vice versa (Lanaspa et al, 2012;Plaideau et al, 2014). Genotoxic stressors including etoposide, doxorubicin, and ionizing radiation also activate AMPK (Fu et al, 2008;Ji et al, 2010;Sanli et al, 2010).…”
Section: Vif Modulates Cellular Energy Homeostasis Via Pp2a-b56 Degramentioning
confidence: 99%